2018
DOI: 10.1039/c8ra03404d
|View full text |Cite|
|
Sign up to set email alerts
|

Green synthesis of Pd nanoparticles supported on reduced graphene oxide, using the extract of Rosa canina fruit, and their use as recyclable and heterogeneous nanocatalysts for the degradation of dye pollutants in water

Abstract: We suggests a convenient synthesis of in situ, ecofriendly and well-dispersed Pd nanoparticles with narrow and small dimension distributions on graphene oxide (GO) using Rosa canina extract as a reducing agent and as the only stabilizer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 71 publications
1
21
0
Order By: Relevance
“…For these reduction reactions the calculated rate constants were 0.52 min −1 and 0.062 min −1 (Fig. S8a and S8b), respectively, which are also consistent with previous reports [52]. The catalytic turn over number (TON) and the turn over frequency (TOF) for…”
Section: (A) Reduction Of Methylene Blue Dyesupporting
confidence: 90%
“…For these reduction reactions the calculated rate constants were 0.52 min −1 and 0.062 min −1 (Fig. S8a and S8b), respectively, which are also consistent with previous reports [52]. The catalytic turn over number (TON) and the turn over frequency (TOF) for…”
Section: (A) Reduction Of Methylene Blue Dyesupporting
confidence: 90%
“…The transmission electron microscopy and energy‐dispersive X‐ray (EDX) analyses were used to prove the nanostructure of Pd NPs/RGO‐ Rosa canina that was prepared again based on our earlier report with a little modification in the resource of palladium ions . The image corresponding to nanocatalyst (Pd NPs/RGO‐ Rosa canina ) at 100 nm indicated that the Pd NPs are well distributed on the surface of reduced GO.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, we have developed the production of Pd NPs supported on reduced graphene oxide (Pd NPs/RGO‐ Rosa canina ) through reduction of the GO and Pd 2+ ions with Rosa canina fruit extracts as a stabilizer and reductant agent . The utilized approach synthesized well‐dispersed Pd NPs on the graphene sheets used to degrade organic dyes in water in the existence of NaBH 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Graphene oxide (GO) and reduced graphene oxide (RGO) are a new class of promising and efficient supports and catalysts, which have been considered by many scientists . GO is a two‐dimensional material derived from graphene sheets with a large number of oxygen‐containing functional groups such as epoxy, hydroxyl and carboxylic groups (Figure ) .…”
Section: Introductionmentioning
confidence: 99%